2023
DOI: 10.1021/acsenergylett.3c00496
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic 100% Silicon Wafer Anode for All-Solid-State Batteries Achieving High Areal Capacity at Room Temperature

Abstract: Silicon is an attractive anode material for all-solid-state batteries (ASSBs) because it has a high energy density and is safer than metallic lithium. Conventional silicon powder composite electrodes have significant internal voids and detrimental interfaces that suppress the lithium transport and lifetime. Here, we demonstrate that surface-treated thin silicon wafers could serve as monolithic additive-free, electrolyte-free, and void-free electrodes that can achieve high areal capacity at room temperature (∼2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…174,175 Additionally, research on low-reactivity silicon anodes is in progress, with studies reporting on their exceptional performance using additive-free, electrolyte-free, and void-free silicon wafer electrodes. 176…”
Section: Discussionmentioning
confidence: 99%
“…174,175 Additionally, research on low-reactivity silicon anodes is in progress, with studies reporting on their exceptional performance using additive-free, electrolyte-free, and void-free silicon wafer electrodes. 176…”
Section: Discussionmentioning
confidence: 99%
“…The silicon wafer can also be reused in all-solid-state batteries (ASSBs). Na et al 73 reported an interesting study where grooved Si wafer presented better performance as an anode in ASSBs, paving a new way for next-generation high-energy ASSBs. Inspired by this work, waste solar cells have the potential to be directly reused in ASSBs with or without a simple surface purification process, avoiding the morphological modification process in the proposed upcycling strategy.…”
Section: Technical Feasibility Of Upcycling Solar Panel Siliconmentioning
confidence: 99%
“…77 As of August 2021, the average spot market price for silicon metal was nearly 50% higher than the annual average price in 2020. 73 Generally, the strategy of upcycling silicon from solar panels to Si-based anodes enriches the secondary use scenarios of silicon, making the solar panel and LIB supply chains more intertwined. Therefore, this strategy can effectively enhance the flexibility and efficiency of silicon supply chains.…”
Section: Supply Chain Analysis Of Upcycling Solar Panel Siliconmentioning
confidence: 99%
“…Si NW use has mostly been examined in Li-ion/Li-metal batteries; however, it has also gained some interest in solid-state batteries (SSBs) as well as alternative alkali-ion batteries (i.e., Na-ion). Recently, various types of Si, such as monolithic, microparticles, , nanoparticles, amorphous films, , and columnar a-Si, have been used with different solid electrolytes (SE), with demonstrations of exceptional performance even with micrometer-sized Si particles. However, the use of nanostructured Si and especially 1D Si morphologies , in SSB is still in its infancy, and a complete mechanistic understanding of the interfacial reactions (especially SEI formation) is required.…”
Section: Si Nws For Beyond-libsmentioning
confidence: 99%